2020
DOI: 10.1002/chem.202001960
|View full text |Cite
|
Sign up to set email alerts
|

Boronate Covalent and Hybrid Organic Frameworks Featuring PIII and P=O Lewis Base Sites

Abstract: Two covalent organic frameworks comprising Lewis basic P III centers and Lewis acidic boron atoms were prepared by poly-condensation reactions of newly obtained tris(4-diisopropoxyborylphenyl)phosphine with 2,3,6,7,10,11hexahydroxytriphenylene and 2,3,6,7-tetrahydroxy-9,10-dimethylanthracene. Obtained materials exhibit significant sorption of dihydrogen (100 cm 3 g À1 at 1 bar at 77 K), methane (20 cm 3 g À1 at 1 bar at 273 K) and carbon dioxide (50 cm 3 g À1 at 1 bar at 273 K). They were exploited as solidsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Generally, there are two routes to introduce the catalyst into COFs, pre-synthetic functionalization and post-synthetic functionalization. 38,39 It is well known that the solubility, spatial conguration and reactivity of linkers containing functional groups are essentially different from those of original linkers, which is very challenging for the synthesis of COFs. 40 In order to avoid these obstacles, the postsynthetic modication strategy has been extensively investigated to introduce catalytic functional groups onto the pore walls of COFs, paving the way for the synthesis of COF supported heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there are two routes to introduce the catalyst into COFs, pre-synthetic functionalization and post-synthetic functionalization. 38,39 It is well known that the solubility, spatial conguration and reactivity of linkers containing functional groups are essentially different from those of original linkers, which is very challenging for the synthesis of COFs. 40 In order to avoid these obstacles, the postsynthetic modication strategy has been extensively investigated to introduce catalytic functional groups onto the pore walls of COFs, paving the way for the synthesis of COF supported heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…3 Clearly, compared with CS, the pyrrolic-N peak of Pd/SCS7 positively shifts 0.2 eV from 400 to 400.2 eV. Meanwhile, a negative shift for Pd 0 , compared with previous reports, 53,54 is observed. These shifts of binding energy indicate the electron transfer from pyrrolic-N to Pd nanoparticles, and electron-rich Pd nanoparticles are beneficial to improve the selectivity of halogenated nitrobenzenes.…”
Section: Resultsmentioning
confidence: 64%
“…[34] Tris(pbromophenyl)phosphine underwent triple halogen-metal exchange and subsequent borylation with triisopropyl borate and treatment with Me 3 SiCl to yield the desired product. It was used in the ester form since the free acid was in equilibrium with the hydrated zwitterion and thus not suitable [56] .…”
Section: Phosphine Monomers For P-cofs and P-pops Synthesismentioning
confidence: 99%
“…The solids were poorly crystalline, showing only short-range order by synchrotron-light PXRD, and porous, with BET surface area of 669 and 530 m 2 /g respectively and broad pore size distribution. [56] Palladium-functionalized BP1 and BP2 were prepared with two different approaches: by polymerizing palladium complexes with phosphine monomers and by PSM of the P-COFs with Pd 2 (dba) 3 . XPS analyses demonstrated that the PSM strategy introduces a larger amount of palladium in the solids but promotes the formation of metal NPs instead of palladium-phosphine complexes.…”
Section: P-cofs and P-popsmentioning
confidence: 99%